2021
DOI: 10.1001/jamacardio.2021.0961
|View full text |Cite
|
Sign up to set email alerts
|

Association of Systolic Blood Pressure Elevation With Disproportionate Left Ventricular Remodeling in Very Preterm-Born Young Adults

Abstract: IMPORTANCE Preterm-born individuals have higher blood pressure with an increased risk of hypertension by young adulthood, as well as potentially adverse cardiac remodeling even when normotensive. To what extent blood pressure elevation affects left ventricular (LV) structure and function in adults born preterm is currently unknown. OBJECTIVE To investigate whether changes observed in LV structure and function in preterm-born adults make them more susceptible to cardiac remodeling in association with blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 30 publications
(72 reference statements)
1
25
0
Order By: Relevance
“…The functional MR velocity indicates the pressure difference between LA and LV in the systole. The elevation of MR velocity after the procedure illustrates that the LV pressure in the systole was elevated, which is correlated with the elevation of FS and GRS [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The functional MR velocity indicates the pressure difference between LA and LV in the systole. The elevation of MR velocity after the procedure illustrates that the LV pressure in the systole was elevated, which is correlated with the elevation of FS and GRS [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that preterm‐born adults are at an increased risk of developing hypertension and are more likely to have greater blood pressure levels than their term‐born peers as early as childhood (Lewandowski et al., 2020), our group has investigated what effect this may have on the observed changes in the LV of young adults born preterm. In a cohort of 468 individuals with CMR imaging, of which 200 were born preterm, it was shown that there was a significant, positive association in both preterm‐ and term‐born young adults between systolic blood pressure and LV mass (Mohamed et al., 2021). In addition to a leftward shift in the regression lines in those born preterm compared to those born at term, there was a stronger association between systolic blood pressure and LV mass in the preterm‐born compared to term‐born young adults.…”
Section: Left Ventricular Response To Systemic Blood Pressure Elevationmentioning
confidence: 99%
“…The effect of prematurity on structural and functional cardiac parameters from birth until young adulthood was summarized by a recent meta‐analysis (Telles et al, 2020). Overall, the cardiac effects of premature birth manifest themselves across the spectrum of developmental stages and include smaller ventricular internal dimensions and impaired systolic and diastolic function (Figure 1) (Flahault et al, 2021; Goss et al, 2020; Huckstep et al, 2018; Kowalski et al, 2016; Lewandowski et al, 2021; Lewandowski, Augustine, et al, 2013; Lewandowski, Bradlow, et al, 2013; Mohamed et al, 2020, 2021; Mohlkert et al, 2018, 2020; Telles et al, 2020). Adults born preterm have since been shown to have greater myocardial diffuse fibrosis, characterized by excessive extracellular volume fraction by CMR, compared to their term‐born counterparts (Lewandowski et al, 2021).…”
Section: Cardiac Phenotype(s) Of Prematuritymentioning
confidence: 99%
“…In addition, cardiovascular risk factors later in life may further impact the geometry and function of the preterm heart. For instance, in a recent CMR imaging study of 468 young adults, of which 200 were preterm‐born, the extent to which blood pressure elevation affected LV remodeling was explored (Mohamed et al, 2021). It was shown that the unique structure and function of the preterm left ventricle was more susceptible to systolic blood pressure elevation.…”
Section: Cardiac Phenotype(s) Of Prematuritymentioning
confidence: 99%